A New Method of Mix Design for Cold Patching Asphalt Mixture - Lv, Songtao; Wang, Shuangshuang; Xia, Chengdong; Liu, Chaochao (Frontiers in Materials, 2020)
The objective of this research was to improve the scientificity of the design method of the cold patching asphalt mixture (CPAM). Firstly, the curing temperature for CPAM was optimized. In addition, based on the traditional Marshall mix design method, the volume parameters of CPAM were converted, and the low-temperature workability index was added. This is the modified Marshall mix design method to determine the optimal asphalt aggregate ratio of CPAM. Then, the initial strength, forming strength, storage stability, water stability, and high-temperature stability of CPAM were tested. The properties of CPAM designed by using the modified Marshall mix design method were compared with those of CPAM designed by using the traditional Marshall mix design method and the empirical formula method. The test results show that the optimal asphalt aggregate ratio of CPAM is 5.38%. The recommended oven curing temperature for the CPAM specimen is 90°C. The initial strength and forming strength of CPAM meet the requirements, and the forming strength can reach about twice the initial strength. The stability of CPAM increases with an increase in storage time. High-temperature performance is good. These properties of CPAM designed by using the modified Marshall mix design method were all superior to those of the CPAM designed by using the traditional Marshall mix design method and the empirical formula method, and the water stability is similar to that of the CPAM designed by the traditional Marshall mix design method. The CPAM designed by using the modified Marshall mix design method shows better road performance, which shows that the modified procedure in this study is feasible and can be recommended as the mix design method for CPAM.